Determination of MSMEs Business Feasibility Decisions using the Profile Matching Method - Maulidah, Salsa Bila Jihan; Sudipa, I Gede Iwan; Fittryani, Yuri Prima; Widiartha, Komang Kurniawan; Winatha, Komang Redy (Politeknik Ganesha Medan, 2024)
Micro and Medium Enterprises (MSMEs) in Bali contribute to the local economy. When operating a business, it is crucial to evaluate the viability of MSME enterprises to enhance the calibre of business offerings and services. Nevertheless, the lack of competence to establish the parameters or criteria for evaluating the viability of a firm poses challenges for MSMEs in decision-making. This study presents a business feasibility assessment model utilising the Profile Matching method to aid in resolving issues and supporting Micro, Small, and Medium Enterprises (MSMEs) in making informed decisions for the long-term viability of their businesses. This study examines the feasibility of MSME businesses using the Profile Matching method. The method involves assessing 13 criteria and selecting from 10 alternatives. The process includes determining initial and target values, weighting criteria, grouping core and secondary factors, calculating total values, and ranking. The final results indicate which MSMEs are feasible and which ones require further evaluation. According to the calculations using the Profile Matching method, MSME 5 has a value of 27.80, indicating its feasibility.